Antiviral effect of vitamin A on norovirus infection via modulation of the gut microbiome - Lee, Heetae (Sci Rep, 2016)
The effect and underlying mechanism of vitamin A on norovirus infection are largely unknown. This study aimed to investigate how vitamin A administration affects the gut microbiome after norovirus infection. Here, we demonstrate that treatment with either retinol or retinoic acid (RA) inhibits murine norovirus (MNV) replication using both in vitro and in vivo models. Compositional changes in the gut microbiome associated with RA administration and/or norovirus infection were also investigated. Oral administration of RA and/or MNV significantly altered intestinal microbiome profiles. Particularly, bacterial species belonging to the Lactobacillaceae families were remarkably increased by MNV inoculation and RA administration, suggesting that the antiviral effects of RA occur via the modulation of specific microbiota. The antiviral causal effect of Lactobacillus was identified and demonstrated using in vitro models in RAW264.7 cells. The antiviral immune response to MNV was mediated by IFN-β upregulation. This study represents the first comprehensive profiling of gut microbiota in response to RA treatment against norovirus infection. Moreover, we conclude that the abundance of Lactobacillus through gut microbiota modulation by RA is at least partially responsible for norovirus inhibition.